Preparation method of flexible heat regulator material based on liquid crystal elastomer-liquid metal composite foam

By preparing liquid crystal elastomer-liquid metal composite foam material, using its thermally reversible deformation and thermal conductivity, the shortcomings of existing thermal regulator materials in mechanical stress and rigidity are solved, and the compatibility of high switching ratio and mechanical flexibility is achieved. It provides an effective material solution for intelligent thermal management of flexible systems.

CN119490692APending Publication Date: 2025-02-21TIANJIN UNIV
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202311050019.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-08-21
Publication Date
2025-02-21

AI Technical Summary

Technical Problem

Existing thermal regulator materials are prone to damage under external mechanical stress or internal thermal stress, and their rigidity does not match emerging flexible systems, making it difficult to achieve compatibility with high switching ratios and mechanical flexibility.

Method used

By preparing flexible thermal regulator materials based on liquid crystal elastomer-liquid metal composite foam, the thermally reversible deformation of liquid crystal elastomer and thermal conductivity of liquid metal are used to form a dual network structure to achieve a wide working temperature window at 40-100℃ High thermal resistance switch ratio within.

Benefits of technology

The maximum thermal resistance switching ratio can reach 3.8, with high switching ratio and mechanical flexibility, and is suitable for intelligent thermal management in flexible energy storage systems, soft robots and other fields.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119490692A_ABST
    Figure CN119490692A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of a flexible heat regulator material based on liquid crystal elastomer-liquid metal composite foam. The preparation method comprises the following three steps: preparation of pre-crosslinked liquid crystal elastomer foam, deformation programming of the liquid crystal elastomer foam and compounding of the liquid crystal elastomer foam and liquid metal. The obtained liquid crystal elastomer-liquid metal composite foam has a thermally induced reversible deformation characteristic, is in a contraction state in a low-temperature region and in an expansion state in a high-temperature region, has a transition temperature window of 40-100 DEG C, has a maximum thermal resistance switch ratio of 3.8, has flexibility below a nematic-isotropic transition temperature (TNI), and has high elasticity above the TNI. The thermal regulator material disclosed by the invention realizes consideration of high switch ratio and mechanical flexibility, and can provide important material support for dynamic and intelligent thermal management of a flexible system in the future.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a method for preparing a flexible heat regulator material based on liquid crystal elastomer-liquid metal composite foam, which can be used for intelligent heat management of flexible energy storage systems, soft robots, wearable devices and space deployable mechanisms, and belongs to the field of thermal functional materials. Background Art

[0002] Thermal management is critical to protect organisms from extreme thermal damage and prevent performance degradation of electronic devices, which is achieved by maintaining a narrow temperature window. Unlike traditional static thermal management schemes, thermal switches with dynamic and variable thermal conductivity can adjust heat flux according to demand, and therefore have great prospects in areas such as battery thermal control, personal thermal management, space regulation, and thermal energy storage. Currently, a lot of work has been devoted to the development of thermal switch materials that can respond to various external stimuli, including external fields (electric, magnetic, optical), mechanical strain, humidity, and electrochemical intercalation. Compared with thermal switches triggered by non-thermal stimuli, thermal regulators are nonlinear thermal devices or materials that can directly respond to temperature and further affect temperature through self-feedback regulation of heat flux, which has the characteristics of intelligent and adaptive thermal management.

[0003] The thermal conductivity of conventional thermal regulators is limited to the critical transition temperature (T crit ), which is usually caused by the transformation of the material's crystal structure. It can be divided into three categories according to the material type and the corresponding mechanism: i) conformational transformation of molecular chains in highly arranged polymers and order transformation in liquid crystal block copolymers, such as in crystalline polyethylene nanofibers, based on T crit The conformational transition near ≈400K, with a high on-off ratio (R on / off ), but the characteristics of the nanoscale limit their macroscopic applications. ii) Phase change materials undergo solid-liquid phase transitions. For example, Shen et al. achieved a switching ratio of ~3.2 in a graphite / hexadecane suspension. This is because the internal stress generated during the crystallization process improves the contact between graphite flakes. However, the solid-state brittleness and liquid fluidity of phase change materials limit their practical applications. iii) Solid-solid transformations of certain metal alloys or transition metal oxide crystalline phases (such as metal-insulator transformations, martensite-austenite transformations, and charge density wave phase transitions, etc.), such as Ni-Mn-In alloys that undergo martensite transformations near room temperature with a switching ratio of 1.5. These phase transitions usually result in a positive temperature coefficient change in thermal conductivity (the thermal conductivity of the high-temperature phase is higher than that of the low-temperature phase), but their switching ratios are relatively low (R on / off <2).

[0004] On the one hand, the inherent brittleness of the material can easily lead to structural damage and functional failure of the thermal regulator under the action of external mechanical stress or internal thermal stress. On the other hand, the rigidity of current thermal regulators makes them incompatible with emerging soft platforms (flexible energy storage systems, soft robots, wearable devices, and space deployable mechanisms, etc.) in terms of mechanical properties. Therefore, how to achieve compatibility between high switching ratio and mechanical flexibility is of great significance for the design and application of soft thermal regulator materials. Summary of the invention

[0005] The purpose of the present invention is to overcome the shortcomings of the prior art and provide a flexible thermal regulator material with a high switching ratio and a preparation method thereof. Based on the thermo-induced reversible deformation of liquid crystal elastomer foam, a soft thermal regulator material is developed by forming a double network structure through composite liquid metal, which achieves a high thermal resistance switching ratio of 3.8 in a wide operating temperature window of 40-100°C and a high thermal resistance switching ratio at the nematic-isotropic transition temperature (T NI ) is flexible below T NI The above has high elasticity.

[0006] The technical purpose of the present invention is achieved through the following technical solutions.

[0007] A flexible heat regulator material based on liquid crystal elastomer-liquid metal composite foam and a preparation method thereof are carried out according to the following steps:

[0008] Step 1, Preparation of Pre-crosslinked Liquid Crystalline Elastomer Foam

[0009] The liquid crystal monomer, flexible spacer, crosslinker, solvent and photoinitiator required for the synthesis of liquid crystal elastomer are mixed. The mixture is dissolved in a hot water bath and stirred evenly. When the white powder is completely dissolved and the mixture becomes clear and transparent, it is immediately taken out and cooled in a cold water bath to prevent gelation. Then the catalyst solution is added and mixed evenly, and an appropriate amount of solution is injected into the mold containing the NaCl salt template, and the liquid crystal monomer solution is pressed into the pores of the NaCl salt template by vacuum-assisted infusion. After reacting at room temperature for 10 to 20 hours, the mold is removed, the solvent toluene is dried in a vacuum oven, and the sample is cut to a predetermined thickness. Then the sample is immersed in distilled water to remove the internal NaCl salt template, and the water is repeatedly changed until the sample floats on the water surface. The water-containing sample is frozen until ice, and then the water is removed by freeze drying to obtain a pre-crosslinked liquid crystal elastomer foam.

[0010] In step 1, the liquid crystal monomer is 1,4-bis-[4-(3-acryloxypropoxy)benzoyloxy]-2-methylbenzene (RM257), the flexible spacer is 3,6-dioxa-1,8-dioctanethiol (EDDET), the crosslinker is pentaerythritol tetrakis(3-mercaptopropionic acid)ester (PETMP), the solvent is toluene, the catalyst is di-n-propylamine, and the photoinitiator is 2-hydroxy-4′-(2-hydroxyethoxy)-2-methylpropiophenone (HHMP).

[0011] In step 1, the ratio of the addition amount of the three polymerizable monomers is calculated by the amount of the substance: liquid crystal monomer: flexible spacer: crosslinking agent = 1: (0.5-0.9): (0.025-0.15). Preferably, liquid crystal monomer: flexible spacer: crosslinking agent = 1: 0.7: 0.075.

[0012] In step 1, the catalyst is a pre-prepared di-n-propylamine / toluene solution with a concentration of 0.5-2 wt %. Calculated by the amount of substance, the amount of di-n-propylamine added is 0.3-0.7 mol % of the total molar number of the three polymerization monomers.

[0013] In step 1, the amount of solvent toluene added is 20-40 wt % of the mass of the liquid crystal monomer RM257.

[0014] In step 1, the amount of photoinitiator HHMP added is 0.5-2 wt % of the mass of the three polymerizable monomers.

[0015] In step 1, the raw material mixture is heated in a hot water bath at a temperature between 70 and 90° C. for 2 to 5 minutes.

[0016] In step 1, the solvent is dried under vacuum at a temperature between 60 and 90° C. for 24 to 48 hours.

[0017] Step 2: Liquid crystal elastomer foam deformation programming

[0018] The pre-crosslinked liquid crystal elastomer foam obtained in step 1 is placed in a specially prepared quartz glass template, and ultraviolet light is used to induce secondary crosslinking under a constant compression state to obtain a liquid crystal elastomer foam material that has been deformed and programmed.

[0019] In step 2, constant compression is performed to 20-50% of the original height. Preferably, constant compression is performed to 30% of the original height.

[0020] In step 2, the wavelength of the ultraviolet light is 365nm and the intensity is 40-100mW / cm 2 , time is 10 to 30 minutes.

[0021] Step 3: Liquid crystal elastomer foam and liquid metal composite

[0022] The deformation-programmed liquid crystal elastomer foam material obtained in step 2 is completely immersed in liquid metal, and vacuum (0.9 bar) is repeatedly applied three times to allow the liquid metal to fill the pores of the liquid crystal elastomer foam. Subsequently, additional liquid metal is squeezed out of the liquid crystal elastomer foam saturated with liquid metal. Finally, the liquid crystal elastomer-liquid metal composite foam is annealed at high temperature to eliminate residual stress.

[0023] In step 3, the liquid metal is a gallium-based alloy having a melting point below room temperature. Preferably, the liquid metal is a gallium-indium alloy with a mass ratio of Ga:In=75.5:24.5.

[0024] In step 3, the liquid metal content retained in the liquid crystal elastomer foam after the extrusion treatment is 0 to 100 wt % of the original saturation content.

[0025] In step 3, the liquid crystal elastomer-liquid metal composite foam is annealed at a temperature of 100 to 180° C. for a time of 10 to 60 minutes.

[0026] The present invention uses liquid crystal monomers and liquid metal as raw materials, first prepares pre-crosslinked liquid crystal elastomer foam by sacrificial salt template method, and then obtains a liquid crystal elastomer foam material with thermo-induced reversible deformation through a secondary crosslinking process, and further compounded with liquid metal to obtain a mechanically flexible thermal regulator material. In the low temperature zone, it is in a contracted state, and a heat conduction path is formed between the internal liquid metals, with high thermal conductivity and low bulk thermal resistance; in the high temperature zone, it is in an expanded state, and the liquid metal network is disconnected into discrete droplets, with low thermal conductivity and high bulk thermal resistance. Its maximum thermal resistance switching ratio can reach 3.8, achieving compatibility between high switching ratio and mechanical flexibility, making up for the shortcomings of existing technologies, and providing a strong material candidate for dynamic and intelligent thermal management of future flexible systems. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1 The present invention is a schematic diagram of the preparation process of the liquid crystal elastomer-liquid metal composite foam heat regulator material.

[0028] Figure 2 Thermal conductivity and thermal resistance of liquid crystal elastomer-liquid metal composite foams with different liquid metal contents at 25°C and 130°C.

[0029] Figure 3 The thermal conductivity and thermal resistance changes and the cycle stability of the liquid crystal elastomer-liquid metal composite foam obtained in Example 2 during the heating and cooling process.

[0030] Figure 4 Schematic diagram of the thermal regulation mechanism of liquid crystal elastomer-liquid metal composite foam. DETAILED DESCRIPTION

[0031] Four embodiments of the present invention are given below to further illustrate the present invention, but not to limit the scope of the present invention, wherein the liquid crystal monomer, the flexible spacer, the cross-linking agent, the solvent, the catalyst, the photoinitiator, the gallium and the indium are all purchased from the market.

[0032] Example 1

[0033] 1) Preparation of pre-crosslinked liquid crystal elastomer foam: Weigh liquid crystal monomer RM257 (1.5 g, 2.546 mmol), flexible spacer EDDET (0.335 g, 1.782 mmol), crosslinker PETMP (0.098 g, 0.191 mmol), solvent toluene (470 mg), photoinitiator HHMP (0.0196 g) and mix. Dissolve the mixture in a hot water bath at 80°C and stir evenly. When the white powder is dissolved and the mixture becomes clear and transparent, take it out immediately and cool it in a cold water bath to prevent gelation. Then add 290 μL of pre-prepared di-n-propylamine / toluene catalyst solution (concentration 1 wt%) and mix well. Pipet 1000 μL of the solution into the mold containing the NaCl salt template, and press the liquid crystal monomer solution into the pores of the NaCl salt template by vacuum-assisted infusion. After reacting at room temperature for 20 hours, remove the mold, dry the solvent toluene in a vacuum oven at 80°C for 24 hours, and cut the sample to a thickness of 10 mm. The sample was then immersed in distilled water to remove the internal NaCl salt template, and the water was changed repeatedly until the sample floated on the water surface. The water-containing sample was frozen until ice formed, and then the water was removed by freeze drying to obtain a pre-crosslinked liquid crystal elastomer foam.

[0034] 2) Liquid crystal elastomer foam deformation programming: The pre-crosslinked liquid crystal elastomer foam obtained in step 1 was placed in a specially made cylindrical quartz glass template (16 mm in diameter), compressed to a thickness of 3 mm, and a second crosslinking was performed using 365 nm ultraviolet light under constant compression, with a light intensity of 40 mW / cm 2 The time is 20 minutes, and the deformation programmed liquid crystal elastomer foam material is obtained. The dynamic thermomechanical analysis shows that the thermally induced reversible deformation of the obtained liquid crystal elastomer foam is 121%.

[0035] 3) Composite of liquid crystal elastomer foam and liquid metal: The deformation-programmed liquid crystal elastomer foam material obtained in step 2 is completely immersed in liquid metal, which is a gallium-indium alloy (Ga: In = 75.5: 24.5). The vacuum is repeatedly drawn three times (0.9 bar) to allow the liquid metal to fill the pores of the liquid crystal elastomer foam. Subsequently, additional liquid metal is squeezed out of the liquid crystal elastomer foam saturated with liquid metal, and the liquid metal content is retained at 25wt% of the original saturated content. Finally, the liquid crystal elastomer-liquid metal composite foam is annealed at 130°C for 30 minutes to eliminate residual stress. The thermal conductivity at 25°C and 130°C is tested by a hot plate method thermal constant analyzer. The thermal conductivity switch ratio of the obtained liquid crystal elastomer-liquid metal composite foam is 1.38, and the thermal resistance switch ratio is 2.80.

[0036] Example 2

[0037] 1) Preparation of pre-crosslinked liquid crystal elastomer foam: Weigh liquid crystal monomer RM257 (1.5 g, 2.546 mmol), flexible spacer EDDET (0.335 g, 1.782 mmol), crosslinker PETMP (0.098 g, 0.191 mmol), solvent toluene (470 mg), photoinitiator HHMP (0.0196 g) and mix. Dissolve the mixture in a hot water bath at 80°C and stir evenly. When the white powder is dissolved and the mixture becomes clear and transparent, take it out immediately and cool it in a cold water bath to prevent gelation. Then add 290 μL of pre-prepared di-n-propylamine / toluene catalyst solution (concentration 1 wt%) and mix well. Pipet 1000 μL of the solution into the mold containing the NaCl salt template, and press the liquid crystal monomer solution into the pores of the NaCl salt template by vacuum-assisted infusion. After reacting at room temperature for 20 hours, remove the mold, dry the solvent toluene in a vacuum oven at 80°C for 24 hours, and cut the sample to a thickness of 10 mm. The sample was then immersed in distilled water to remove the internal NaCl salt template, and the water was changed repeatedly until the sample floated on the water surface. The water-containing sample was frozen until ice formed, and then the water was removed by freeze drying to obtain a pre-crosslinked liquid crystal elastomer foam.

[0038] 2) Liquid crystal elastomer foam deformation programming: The pre-crosslinked liquid crystal elastomer foam obtained in step 1 was placed in a specially made cylindrical quartz glass template (16 mm in diameter), compressed to a thickness of 3 mm, and a second crosslinking was performed using 365 nm ultraviolet light under constant compression, with a light intensity of 40 mW / cm 2 The time is 20 minutes, and the deformation programmed liquid crystal elastomer foam material is obtained. The dynamic thermomechanical analysis shows that the thermally induced reversible deformation of the obtained liquid crystal elastomer foam is 121%.

[0039] 3) Composite of liquid crystal elastomer foam and liquid metal: The deformation-programmed liquid crystal elastomer foam material obtained in step 2 is completely immersed in liquid metal, which is a gallium-indium alloy (Ga: In = 75.5: 24.5). The vacuum is repeatedly drawn three times (0.9 bar) to allow the liquid metal to fill the pores of the liquid crystal elastomer foam. Subsequently, additional liquid metal is squeezed out of the liquid crystal elastomer foam saturated with liquid metal, and the liquid metal content is retained at 50wt% of the original saturated content. Finally, the liquid crystal elastomer-liquid metal composite foam is annealed at 130°C for 30 minutes to eliminate residual stress. The thermal conductivity of the liquid crystal elastomer-liquid metal composite foam is tested at 25°C and 130°C by a hot plate method thermal constant analyzer. The thermal conductivity switching ratio of the obtained liquid crystal elastomer-liquid metal composite foam is 1.96, and the thermal resistance switching ratio is 3.87.

[0040] Example 3

[0041] 1) Preparation of pre-crosslinked liquid crystal elastomer foam: Weigh liquid crystal monomer RM257 (1.5 g, 2.546 mmol), flexible spacer EDDET (0.335 g, 1.782 mmol), crosslinker PETMP (0.098 g, 0.191 mmol), solvent toluene (470 mg), photoinitiator HHMP (0.0196 g) and mix. Dissolve the mixture in a hot water bath at 80°C and stir evenly. When the white powder is dissolved and the mixture becomes clear and transparent, take it out immediately and cool it in a cold water bath to prevent gelation. Then add 290 μL of pre-prepared di-n-propylamine / toluene catalyst solution (concentration 1 wt%) and mix well. Pipet 1000 μL of the solution into the mold containing the NaCl salt template, and press the liquid crystal monomer solution into the pores of the NaCl salt template by vacuum-assisted infusion. After reacting at room temperature for 20 hours, remove the mold, dry the solvent toluene in a vacuum oven at 80°C for 24 hours, and cut the sample to a thickness of 10 mm. The sample was then immersed in distilled water to remove the internal NaCl salt template, and the water was changed repeatedly until the sample floated on the water surface. The water-containing sample was frozen until ice formed, and then the water was removed by freeze drying to obtain a pre-crosslinked liquid crystal elastomer foam.

[0042] 2) Liquid crystal elastomer foam deformation programming: The pre-crosslinked liquid crystal elastomer foam obtained in step 1 was placed in a specially made cylindrical quartz glass template (16 mm in diameter), compressed to a thickness of 3 mm, and a second crosslinking was performed using 365 nm ultraviolet light under constant compression, with a light intensity of 40 mW / cm 2 The time is 20 minutes, and the deformation programmed liquid crystal elastomer foam material is obtained. The dynamic thermomechanical analysis shows that the thermally induced reversible deformation of the obtained liquid crystal elastomer foam is 121%.

[0043] 3) Composite of liquid crystal elastomer foam and liquid metal: The deformation-programmed liquid crystal elastomer foam material obtained in step 2 is completely immersed in liquid metal, which is a gallium-indium alloy (Ga: In = 75.5: 24.5). The vacuum is repeatedly drawn three times (0.9 bar) to allow the liquid metal to fill the pores of the liquid crystal elastomer foam. Subsequently, additional liquid metal is squeezed out of the liquid crystal elastomer foam saturated with liquid metal, and the liquid metal content is retained at 75wt% of the original saturated content. Finally, the liquid crystal elastomer-liquid metal composite foam is annealed at 130°C for 30 minutes to eliminate residual stress. The thermal conductivity at 25°C and 130°C is tested by a hot plate method thermal constant analyzer. The thermal conductivity switch ratio of the obtained liquid crystal elastomer-liquid metal composite foam is 1.56, and the thermal resistance switch ratio is 2.87.

[0044] Example 4

[0045] 1) Preparation of pre-crosslinked liquid crystal elastomer foam: Weigh liquid crystal monomer RM257 (1.5 g, 2.546 mmol), flexible spacer EDDET (0.335 g, 1.782 mmol), crosslinker PETMP (0.098 g, 0.191 mmol), solvent toluene (470 mg), photoinitiator HHMP (0.0196 g) and mix. Dissolve the mixture in a hot water bath at 80°C and stir evenly. When the white powder is dissolved and the mixture becomes clear and transparent, take it out immediately and cool it in a cold water bath to prevent gelation. Then add 290 μL of pre-prepared di-n-propylamine / toluene catalyst solution (concentration 1 wt%) and mix well. Pipet 1000 μL of the solution into the mold containing the NaCl salt template, and press the liquid crystal monomer solution into the pores of the NaCl salt template by vacuum-assisted infusion. After reacting at room temperature for 20 hours, remove the mold, dry the solvent toluene in a vacuum oven at 80°C for 24 hours, and cut the sample to a thickness of 10 mm. The sample was then immersed in distilled water to remove the internal NaCl salt template, and the water was changed repeatedly until the sample floated on the water surface. The water-containing sample was frozen until ice formed, and then the water was removed by freeze drying to obtain a pre-crosslinked liquid crystal elastomer foam.

[0046] 2) Liquid crystal elastomer foam deformation programming: The pre-crosslinked liquid crystal elastomer foam obtained in step 1 was placed in a specially made cylindrical quartz glass template (16 mm in diameter), compressed to a thickness of 3 mm, and a second crosslinking was performed using 365 nm ultraviolet light under constant compression, with a light intensity of 40 mW / cm 2 The time is 20 minutes, and the deformation programmed liquid crystal elastomer foam material is obtained. The dynamic thermomechanical analysis shows that the thermally induced reversible deformation of the obtained liquid crystal elastomer foam is 121%.

[0047] 3) Composite of liquid crystal elastomer foam and liquid metal: The deformation-programmed liquid crystal elastomer foam material obtained in step 2 is completely immersed in liquid metal, which is a gallium-indium alloy (Ga: In = 75.5: 24.5). The vacuum is repeatedly drawn three times (0.9 bar) to allow the liquid metal to fill the pores of the liquid crystal elastomer foam. There is no need to extrude the liquid metal, and the liquid metal content is retained at 100wt% of the original saturated content. Finally, the liquid crystal elastomer-liquid metal composite foam is annealed at 130°C for 30 minutes to eliminate residual stress. The thermal conductivity of the liquid crystal elastomer-liquid metal composite foam is tested at 25°C and 130°C by a hot plate method thermal constant analyzer. The thermal conductivity switch ratio of the obtained liquid crystal elastomer-liquid metal composite foam is 1.60, and the thermal resistance switch ratio is 2.76.

[0048] According to the present invention, by adjusting the process parameters, the preparation of liquid crystal elastomer-liquid metal composite foam material can be achieved, and it is in a contracted state in the low temperature zone and in an expanded state in the high temperature zone, with a transition temperature range of 40-100°C, a thermal resistance switching ratio of up to 3.8, and a reversible cycle, so as to achieve a balance between high switching ratio and mechanical flexibility of the thermal regulator material.

[0049] The present invention is described above by way of example. It should be noted that, without departing from the core of the present invention, any simple deformation, modification or other equivalent replacement that can be made by those skilled in the art without inventive effort falls within the protection scope of the present invention.

Claims

1. A method for preparing a flexible heat regulator material based on liquid crystal elastomer-liquid metal composite foam, characterized in that The preparation steps are as follows: 1) Preparation of pre-crosslinked liquid crystal elastomer foam: Mix the liquid crystal monomer, flexible spacer, crosslinker, solvent and photoinitiator required for the synthesis of liquid crystal elastomer. Dissolve the mixture in a hot water bath and stir evenly. When the white powder is completely dissolved and the mixture becomes clear and transparent, take it out immediately and cool it in a cold water bath to prevent gelation. Then add the catalyst solution and mix it evenly. Pipet an appropriate amount of solution and inject it into the mold containing the NaCl salt template. Press the liquid crystal monomer solution into the pores of the NaCl salt template by vacuum-assisted infusion. After reacting at room temperature for 10 to 20 hours, remove the mold, dry the solvent toluene in a vacuum oven, and cut the sample to a predetermined thickness. Then soak the sample in distilled water to remove the internal NaCl salt template, and change the water repeatedly until the sample floats on the water surface. Freeze the water-containing sample until it is frozen, and then remove the water by freeze drying to obtain a pre-crosslinked liquid crystal elastomer foam. 2) Liquid crystal elastomer foam deformation programming: The pre-crosslinked liquid crystal elastomer foam obtained in step 1 is placed in a specially prepared quartz glass template, and a secondary crosslinking is initiated by ultraviolet light under a constant compression state to obtain a liquid crystal elastomer foam material that has been deformation programmed. 3) Composite of liquid crystal elastomer foam and liquid metal: The deformation-programmed liquid crystal elastomer foam material obtained in step 2 is completely immersed in liquid metal, and vacuum (0.9 bar) is repeatedly applied three times to allow the liquid metal to fill the pores of the liquid crystal elastomer foam. Subsequently, additional liquid metal is squeezed out of the liquid crystal elastomer foam saturated with liquid metal. Finally, the liquid crystal elastomer-liquid metal composite foam is annealed at high temperature to eliminate residual stress.

2. The preparation method according to claim 1, characterized in that In step 1), the liquid crystal monomer is 1,4-bis-[4-(3-acryloxypropoxy)benzoyloxy]-2-methylbenzene (RM257), the flexible spacer is 3,6-dioxa-1,8-dioctanethiol (EDDET), the crosslinker is pentaerythritol tetrakis(3-mercaptopropionic acid)ester (PETMP), the solvent is toluene, the catalyst is di-n-propylamine, and the photoinitiator is 2-hydroxy-4′-(2-hydroxyethoxy)-2-methylpropiophenone (HHMP).

3. The preparation method according to claim 1, characterized in that In step 1), the ratio of the added amount of the three polymerized monomers is calculated by the amount of the substance: liquid crystal monomer: flexible spacer: cross-linking agent = 1: (0.5-0.9): (0.025-0.15); the added amount of solvent toluene is 20-40wt% of the mass of the liquid crystal monomer RM257; the added amount of the photoinitiator HHMP accounts for 0.5-2wt% of the mass of the three polymerized monomers; the raw material mixture is heated in a hot water bath at a temperature between 70 and 90° C. for 2 to 5 minutes; and the vacuum drying solvent is dried at a temperature between 60 and 90° C. for 24 to 48 hours.

4. The preparation method according to claim 1, characterized in that In step 2), the compression is constant to 20-50% of the original height; the wavelength of the ultraviolet light is 365nm, and the intensity is 20-100mW / cm 2 , time is 10 to 30 minutes.

5. The preparation method according to claim 1, characterized in that In step 3), the liquid metal is a gallium-based alloy with a melting point below room temperature, the retained liquid metal content is 0-100wt% of the original saturated content, and the annealing temperature of the liquid crystal elastomer-liquid metal composite foam is 100-180°C for 10-60min.

6. A liquid crystal elastomer-liquid metal composite foam material prepared according to the preparation method according to any one of claims 1 to 5.

7. Use of the liquid crystal elastomer-liquid metal composite foam material according to claim 6 in the field of heat regulation.

Citation Information

Cited By

  • Foam liquid crystal elastomer for enhancing energy absorption by utilizing microsphere-induced shear deformation as well as preparation method and application of foam liquid crystal elastomer

    CN121825041A